Parametric analysis of liquid storage tanks base isolated by curved surface sliding bearings - Abali, Emre; Uckan, Eren (Elsevier Sci Ltd, 2010)
Curved surface sliding bearings, which are usually called as friction pendulum system (FPS) are commonly used for base isolation of liquid storage tanks since the period of the isolation system is independent of the storage level. However the restoring force and the damping at the isolation system are functions of axial load which changes during an earthquake excitation. This change might be in appreciable amounts especially for the tanks with high aspect ratios. The present paper focuses on earthquake performances of both broad and slender tanks base isolated by FPS bearings. The effects of overturning moment and vertical acceleration on axial load variation at the bearings are considered. The efficiency of the isolation system is investigated by analyzing the effects of various parameters such as; (i) isolation period, (ii) tank aspect ratio and (iii) coefficient of friction. The Haroun and Housner's three-degrees-of-freedom lumped mass model was used to solve the governing equations of motion in which convective, impulsive and rigid masses were included. A number of selected ground motions were considered and the results were compared to those of non-isolated cases. As a result, base isolation was found to be effective in reducing the base shear values for both broad and slender tanks without significantly affecting the sloshing displacements of the broad ones. The efficiency was even more pronounced for slender tanks subjected to near fault ground motions for isolation periods above 3s. This specific value of isolation period also eliminated possible design problems arising from under-estimation of base shear values (up to 40%) due to ignoring the effects of axial load variation in lower isolation periods. Overturning effects should not be ignored especially for tanks with high aspect ratios (S) and being subjected to near fault ground motion. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Base isolation; Sliding bearings; Liquid storage tanks; Seismic response